2004
DOI: 10.1029/2004wr003295
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional steady unsaturated flow through embedded elliptical layers

Abstract: [1] New analytic element solutions are presented for unsaturated, two-dimensional steady flow in vertical planes that include nonoverlapping impermeable elliptical layers and elliptical inhomogeneities. The hydraulic conductivity, which is represented by an exponential function of the pressure head, differs between the inside and outside of an elliptical inhomogeneity; both the saturated hydraulic conductivity and water retention parameters are allowed to differ between the inside and outside. The Richards equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…However, a closer examination showed that when a streamline approaches a macropore, it diverts around the macropore because at this pressure the hydraulic conductivity of the macropores is essentially zero, and the macropore thereby offers a very resistant pathway to flow. This effect of streamline deflection around unsaturated highly permeable objects has been clearly demonstrated and described by Bakker & Nieber (2005).…”
Section: Resultsmentioning
confidence: 84%
“…However, a closer examination showed that when a streamline approaches a macropore, it diverts around the macropore because at this pressure the hydraulic conductivity of the macropores is essentially zero, and the macropore thereby offers a very resistant pathway to flow. This effect of streamline deflection around unsaturated highly permeable objects has been clearly demonstrated and described by Bakker & Nieber (2005).…”
Section: Resultsmentioning
confidence: 84%
“…This case is for the flux (rainfall) rate equal to 0Ð025 m/day Table I. The rise in pore water pressure at the blocked end of macropores M1 and M2 are illustrated in Figure 7a and b for some of the cases result for unsaturated flow around embedded texturally contrasting material shown by Bakker and Nieber (2005). For this case, the saturated zone occupies only a small volume near the toe of the slope, and all the macropores lie within the overlying unsaturated zone (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…3.2]. Bakker [28,51] and Bakker and Nieber [8] derived elliptical AEM elements for the modified Helmholtz equation. A significant difference between their elliptical AEM solutions and that given here is the presence of the complex Laplace parameter, p, which becomes large at small time; this is because p and t are multiplicative arguments to the exponential in the definition of the Laplace transform (e.g.…”
Section: Elliptical Elementsmentioning
confidence: 98%
“…The parameter q is specified through the aquifer properties, element geometry, and p, while ω is determined to make the solution to (26a) periodic on π ≤ ψ < −π . The special functions that are solutions to (26a) and (26b) are Mathieu functions; see [8,54,55] for characteristic functional plots. Solutions to (25) for Re(q) < 0 arē …”
Section: Elliptical Elementsmentioning
confidence: 99%
See 1 more Smart Citation